EPIDEMIOLOGY OF ACQUIRED APLASTIC ANAEMIA IN PAKISTAN - Ehsan, Ayesha; Shah, Shahida Amjad Riaz; Ibrahim, Tayyaba (Journal of Ayub Medical College Abbottabad, 2011)
Background: Acquired aplastic anaemia is a rare disease which results in morbidity and mortality at a young age. This study was carried out to determine the clinical presentation, haematological parameters and association factors of acquired aplastic anaemia in a cohort of Pakistani patients. Methods: This was a cross-sectional study conducted at Haematology Department, Shaikh Zayed Hospital, Lahore over 7 years from June 2000 to July 2007. Eighty-two patients of acquired aplastic anaemia were enrolled in the study by non-probability purposive sampling. Their diagnosis was confirmed by complete blood count, bone marrow aspirate and trephine biopsy. The cohort was classified on the basis of severity and the epidemiological, clinical and haematological parameters were analysed. Results: Of the 82 enrolled patients of acquired aplastic anaemia, 49 (59.8%) were males and 33 (40.2%) were females. Mean age of the patients was 27.93±18.7 years with a range of 1-80 years. The male to female ratio was 1.48:1. Bone marrow cellularity was less than 25 % in 31 (38.0%) cases and between 25-30% in 51 (62%) of patients. Most of the cases were clinically severe aplastic anaemia (68%). In 62 (76%) of the cases no association factors predisposing to aplastic anaemia could be identified. Conclusion: Acquired Aplastic anaemia is a disease of all ages. In the second decade and the elderly predominantly severe clinical stages were seen. Males presented at a younger age while females presented at all ages with a somewhat similar incidence. No association factors of Aplastic Anaemia could be identified in majority of the patients. Keywords: Aplastic anaemia, epidemiology, clinical staging